An Exploration of Femininity, Masculinity, and Racial Prejudices in Herland. (22nd November 2018) - Bowers, Elinor
Abstract: Charlotte Perkins Gilman (1860–1935) helped spearhead the fin de siècle and early 20 th ‐century women's rights movement and significantly contributed to the feminist literary genre with The Yellow Wallpaper (1892). Despite her dedication to the women's movement and contributions to feminist literature, her novel Herland (1915) features problematic undertones of racism, elitism, and masculine degradation. Within recent years, feminism has become a term that is synonymous with inclusivity, with a focus on intersectionality and the rights of not only women but others who have been disenfranchised by race, religious affiliation, sexuality, socioeconomic status, or gender identification. Given modern feminism's focus on diversity, the racist undertones and focus on gender separatism in Herland places Gilman outside the feminist literary genre, particularly as it has been defined in recent decades.